ANALISIS PENGARUH PERTUMBUHAN PERUSAHAAN, KUALITAS AUDIT, OPINION SHOPPING, DAN KONDISI KEUANGAN PERUSAHAAN TERHADAP KEMUNGKINAN PENERIMAAN OPINI AUDIT GOING CONCERN - Syifa Budi Hananto, 07.05.52.0153; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2014)
The existence of the entity must maintain the viability of these entities from the crisis that hit the world economy globalization. Bankruptcy experienced by an entity can be seen from the financial statements. Consideration of an auditor in expressing an opinion on the financial statements. This research is purposed to analyze the effect of company growth, audit quality, opinion shopping, and financial condition towards audit going concern opinion. Sample of this research are the companies that listed on BEI on the years 2009-2011. Data used are secondary data and data technique is logistic regression. Based on the result we can conclude that company growth, Audit quality, Opinion shopping, Financial condition do not have significant effect toward audit going concern opinion.Keywords: company growth, audit quality, opinion shopping, and financial condition, audit going concern opinion